2013
DOI: 10.1186/1475-9276-12-45
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in child mortality trends: what is the evidence from disadvantaged states in India? the case of Orissa and Madhya Pradesh

Abstract: IntroductionThe Millennium Development Goals prompted renewed international efforts to reduce under-five mortality and measure national progress. However, scant evidence exists about the distribution of child mortality at low sub-national levels, which in diverse and decentralized countries like India are required to inform policy-making. This study estimates changes in child mortality across a range of markers of inequalities in Orissa and Madhya Pradesh, two of India’s largest, poorest, and most disadvantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Consistent with previous research (Dommaraju et al 2008;June et al 2011;Mohindra et al 2006;Nguyen et al 2013;Singh et al 2013;Singh-Manoux et al 2008;Subramanian et al 2006aSubramanian et al , 2006b, we find that despite large improvements in health conditions and reductions in mortality in India in recent years, children from lower castes continue to experience higher mortality than those from forward castes. Estimates obtained from the Cox Proportional Hazards Model show that in NFHS-2, with mother's age and child's sex controlled, OBC, Dalit, and Adivasi children are 23, 32, and 27 per cent more likely, respectively, than forward-caste children to die in the first year of life.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous research (Dommaraju et al 2008;June et al 2011;Mohindra et al 2006;Nguyen et al 2013;Singh et al 2013;Singh-Manoux et al 2008;Subramanian et al 2006aSubramanian et al , 2006b, we find that despite large improvements in health conditions and reductions in mortality in India in recent years, children from lower castes continue to experience higher mortality than those from forward castes. Estimates obtained from the Cox Proportional Hazards Model show that in NFHS-2, with mother's age and child's sex controlled, OBC, Dalit, and Adivasi children are 23, 32, and 27 per cent more likely, respectively, than forward-caste children to die in the first year of life.…”
Section: Discussionsupporting
confidence: 92%
“…These surveys have also allowed researchers to carry out micro-level multivariate analyses, with the aim of disentangling the effects of caste and socioeconomic background on mortality (Das et al 2010;Dommaraju et al 2008;June et al 2011;Mohindra et al 2006;Nguyen et al 2013;Singh-Manoux et al 2008;Subramanian et al 2006aSubramanian et al , 2006b). These studies typically use logit models, with infant and child mortality as the outcome variable, caste as the primary independent variable, and various parental characteristics as control variables.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Better socioeconomic and health conditions have been recognized as protective factors against death, particularly from infectious diseases (18) (19) (20) . Only the number of primary health care units was associated with lower case fatality rates, which suggests that access to primary care health professionals may reduce the DHF case fatality rate.…”
Section: Discussionmentioning
confidence: 99%
“…A growing literature has emerged to study the trends of child mortality, and its determinants, in a wide range of countries (see for instance: Dallolio et al, 2012;Feng, et al, 2012;Amouzou et al, 2012;Nattey et al, 2013;Nguyen et al, 2013). For example, Nguyen et al (2013) estimated the change in child mortality rates in two of India's largest and poorest states over the period 1990-2007 found that although there was a decline in child mortality rates at the national level, there were considerable disparities across socio-economic groups, ethnicities, districts, and wealth. In a cross sectional study, Nattey et al (2013) investigated the relationship between household socio-economic status and under-5 mortality, and examined the risk factors associated with under-five mortality in Tanzania.…”
Section: Literature Reviewmentioning
confidence: 99%